Management of the Yellow Book Reading Acceleration Program through the Umdati Method in Islamic Boarding Schools - Soleh, Badrus; Astri Norisa Irfandari (LP2M UIN Kiai Haji Achmad Siddiq Jember, 2025)
Learning to read the yellowIslamic classic books in pesantren often faces obstacles such as complicated Arabic grammar, texts without harakat, and traditional teaching methods that take years. This study analyzes the management of the accelerated yellowclassic book reading program using the Umdati method at Darul Hijrah Pamekasan Islamic Boarding School. Using a descriptive qualitative approach with purposive sampling, data were collected from caregivers, program managers, and santri through interviews, observation, and documentation. Analysis followed the Miles and Huberman interactive model. The findings show that the Umdati-based program effectively shortens the learning period from several years to about 12 months by optimizing three key management functions. Planning is guided by the SMART framework, which targets mastery of basic nahwu in 5 months. The Umdati method simplifies the classical nahwu material into 16 pages, with a composition of 30% theory and 70% practice. The implementation is carried out in five sessions every day using intermittent repetition to strengthen memory. Evaluation is done through formative (daily, weekly, monthly) and summative (end of program) assessments. The success of this program shows that innovation in pesantren education can be done without sacrificing traditional values and learning ethos.